El desarrollo de operaciones de pensamiento y su influencia en el aprendizaje de los contenidos del bloque numérico de matemática en el noveno año de educación general básica de la unidad educativa La Inmaculada de la ciudad y provincia de Loja, período lectivo 2012-2013. Lineamientos alternativos - Sozoranga Guaman, Jenny Isabel (2014)
How can we improve learning levels the number pad in Math with students Ninth Year Basic Education? was the question guiding this research. This research work was carried out under the specific objectives of: identify the main difficulties faced by students in the development of processes with operations on the numeric keypad; establish the theoretical approaches that allow to relate the mental operations in the learning process on the numeric keypad with the students of the Ninth Year of EGB, also implement a system of mental operations actions in the contents corresponding to the new block of Ninth Year of EGB. Through scientific information gathered the importance of the development of the operations of thought in the learning process is shown, as are the main knowledge base to generate more lasting, meaningful and productive learning. Hence the importance that teachers know and apply the activities, actions and resources that facilitate this process to achieve the desired success. Through field research could be detected Mathematics teachers Ninth Year of Basic Education, not work with operations of thought, but rather demonstrate the procedures and students learn it mechanically. It was also found that the development of the operations of thought affect the learning of students. The results related to the scientific content, verify compliance with the objectives in the project.